Inferring inlet morphodynamics and hydraulic parameters from tidal records: A case study of four closure events of Avoca Lake, Australia - Vu, Thi Thu Thuy (2020)
The present paper applies a 24.5 hour moving window to analyse tidal records for Avoca Lake, Australia, to infer the morphodynamic time scales as well as tidal response functions for four closure events. This paper includes modifications to the method presented in Thuy et al. (2012) with de-trending before harmonic analysis, resulting in improved results. Compared with Hinwood & McLean’s 14day window, the 24.5 hour moving window ensures reasonable accuracy of results, clearly showing the variation under short rapid change of weather such as storms or floods and less distraction from too many components. The analysis shows that the inlet closing process tends to begin during the neap tidal phase and takes 1 to 4 days except during rain fall or storm wave events which lengthen the closing process. Harmonic analysis for 4 events shows that the response of the dominant semi-diurnal component is quite stable while the subordinate diurnal response is much more erratic.